Application of the method of averaging to the problems of optimal control for ordinary differential equations on the semiaxis - Kichmarenko, O. D. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
The method of averaging is applied to the nonlinear and linear (with respect to control) problems of optimal control onthe semiaxis with small parameter and rapidly oscillating coefficients. It is shown that the solutions of the exact problemconverge to the solutions of the averaged problem.